2017
DOI: 10.1103/physreva.96.052121
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range-tunable Dirac-cone band structure in a chiral-time-symmetric non-Hermitian system

Abstract: We establish a connection between an arbitrary Hermitian tight-binding model with chiral (C) symmetry and its non-Hermitian counterpart with chiral-time (CT ) symmetry. We show that such a kind of non-Hermitian Hamiltonian is pseudo-Hermitian. The eigenvalues and eigenvectors of the non-Hermitian Hamiltonian can be easily obtained from those of its parent Hermitian Hamiltonian. It provides a way to generate a class of non-Hermitian models with a tunable full real band structure by means of additional imaginary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Unlike the expectation value of Pauli matrix σ α in the usual study [26], σ α k,0 = 0 for all α and α=x,y,z…”
Section: Ep Dynamics and Periodic Drivingmentioning
confidence: 75%
“…Unlike the expectation value of Pauli matrix σ α in the usual study [26], σ α k,0 = 0 for all α and α=x,y,z…”
Section: Ep Dynamics and Periodic Drivingmentioning
confidence: 75%
“…In recent years, it has been attracted much attention and extensive studies have been demonstrated [41][42][43][44][45][46] . The degenerate zero modes take the role of topological invariant in the infinite N limit and are explicitly expressed as…”
Section: A Ssh Chainmentioning
confidence: 99%
“…Non-Hermitian topological systems with PT symmetry are of primary focus [76][77][78][79][80][81][82]. Other symmetries, such as chiral-time (CT ) and charge-parity (CP) symmetries, have been investigated [24,41,48,83,84]. The topological aspects of non-Hermitian systems, including edge modes [84,85], topological invariant [63,[86][87][88][89][90][91][92], band theory [92][93][94][95], topological pumping [56,59,[96][97][98], classification [99][100][101][102][103][104][105], high-order non-Hermitian topological systems [106][107][108][109][110][111], * jinliang@nankai.edu.cn semimetals [112][113][114]…”
Section: Introductionmentioning
confidence: 99%